A simple Fe3+/bisulfite system for rapid degradation of sulfamethoxazole. Issue 50 (17th August 2020) - Wang, Shixiang; Wang, Guangsheng; Fu, Yongsheng; Wang, Hongbin; Liu, Yiqing
Abstract : Sulfate radical (SO4 ˙ − ) based oxidation technologies have been widely used in the remediation of antibiotic-containing wastewater. Abstract : Sulfate radical (SO4 ˙ − ) based oxidation technologies have been widely used in the remediation of antibiotic-containing wastewater. Activated persulfates are efficient reagents for achieving SO4 ˙ −, but the storage and transportation of concentrated persulfates present associated safety issues. In this study, bisulfite (BS) was used as an alternative precursor for replacing persulfates, and a simple advanced oxidation system (Fe 3+ /BS) for generating SO4 ˙ − and hydroxyl radical (HO˙) was formulated and evaluated for removing sulfamethoxazole (SMX) from contaminated water. The initial pH, dosages of Fe 3+ and BS, as well as the water matrix were investigated to improve the SMX degradation. The results indicated that 1 μmol L −1 SMX was completely removed within 5 min at optimum initial pH of 4.0, Fe 3+ dosage of 10 μmol L −1, BS dosage of 100 μmol L −1 and temperature of 25 °C. The presence of HCO3 − and natural organic matter (NOM) showed obviously negative effects on SMX degradation, while Cu 2+ could slightly promote the degradation of SMX if its concentration was in an appropriate range (∼1 μmol L −1 ). Scavenger quenching experiments confirmed the presence of SO4 ˙ − and HO˙, which resulted in efficient SMX degradation in the Fe 3+ /BS system. During the radical chain reactions, Fe 2+ and Fe 3+ could be converted into each other to form self-circulation in this system. The degradation pathway of SMX by Fe 3+ /BS was proposed including hydroxylation and bond cleavage.